Estrategias de marketing para la comercialización de teja elaborada a base de barro en la parroquia La Victoria del cantón Pujilí, provincia de Cotopaxi. - Monge Mogro, Verónica Patricia (2020)
This research is developed with the objective of designing marketing strategies for the commercialization of clay-based tiles in the parish La Victoria-Pujilí, since the market niche has not been technically defined, the lack of knowledge of the producers prevent from carrying out an adequate study of the environment, which has made it tough to locate potential clients. This research is quantitative, because it was necessary to collect data, analyze it and describe it in order to respond to the problem proposed. The techniques used for this investigation are direct observation and surveys. Using direct observation, the researcher went to the workshops, warehouses and the association, helping to identify the strengths, opportunities, weaknesses and threats that impact the commercialization of the roof tiles. The survey was structured with 15 yes/no questions in order to determine the specific needs, tastes and preferences of potential customers and to avoid bias in the data collected. Considering that not everyone would agree to answer the survey, a sample of 87 individuals was taken. The method applied is analytical. Thus, analysis and interpretation was carried out on the results obtained; In this way, it was determined that, merchants have few explored market niches, incur high production costs and low utility; This goes along with external factors such as changes in economic, tax and labor policies that influence negatively on the development of its productive activity, affecting its local growth. For that reason, 13 marketing strategies were designed, based on the marketing mix (Product, Price, Promotion, Place, Person), and the total budget amounts to $ 26,633.00.